An optimized product-enhanced reverse transcriptase assay for sensitive and quantitative detection of HIV viral load and phenotypic drug resistance - Dorothy K. Mims; Megan M. Chang; Ayokunle O. Olanrewaju (Journal of Clinical Microbiology, 2026)
ABSTRACT The World Health Organization (WHO) recommends human immunodeficiency virus (HIV) drug resistance testing (DRT), but current tests are too complex and expensive for routine use. Genotypic DRT is challenging to interpret because of the growing list of mutations responsible for HIV drug resistance. Although phenotypic DRT is simpler to interpret, it requires slow and labor-intensive viral culture. Phenotypic tests that measure the activity of isolated HIV enzymes are faster and less labor-intensive, but none have yet met the 2023 WHO Target Product Profile (TPP) for HIV DRT. Here, we present an optimized product-enhanced reverse transcriptase (PERT) assay for sensitive and quantitative detection of HIV viral load and drug resistance. PERT combines complementary DNA (cDNA) synthesis by HIV-reverse transcriptase (HIV-RT) with cDNA amplification and detection by quantitative PCR (qPCR). We established sensitive detection down to 10 HIV-RT molecules in a 25 µL sample corresponding to a viral load of ~10 HIV RNA copies/mL. We demonstrated the assay’s feasibility for phenotypic DRT using lamivudine-5′-triphosphate (3TC-TP)—to which the M184V mutation confers high-level resistance—and quantified 3TC-TP inhibition using the difference in cDNA produced between drug and no-drug conditions. We surpassed WHO minimal analytical sensitivity requirements (20% low-abundance variant detection) by differentiating 10% M184V HIV-RT fractions in heterogeneous mixtures (1,000 total HIV-RT, viral load ~2,500 copies RNA/mL). Finally, we showed that PERT could detect resistance to existing and emerging RT inhibitors, including tenofovir-diphosphate (TFV-DP), doravirine (DOR), and islatravir (ISL)-TP. IMPORTANCE Although antiretroviral therapy can effectively treat and prevent HIV infection, treatment efficacy and global control of the HIV epidemic are threatened by rising rates of HIV drug resistance. Inexpensive and decentralized HIV drug resistance testing (DRT) could facilitate surveillance efforts to understand the prevalence of HIV drug resistance in local and global contexts. This need is especially timely and pressing considering anticipated increased rates of HIV acquisition and drug resistance due to the reductions in global HIV services driven by recent funding cuts. Our optimized product-enhanced reverse transcriptase (PERT) assay for simultaneous viral load and phenotypic drug resistance quantification is fast (~2 h), sensitive, and accurate. We can also leverage existing RT-qPCR instruments used for viral load measurement to significantly improve access to HIV drug resistance monitoring and tailored regimen selection.